Interactions between circular vortex-rings and free-surfaces - Lim, Xin Le (Nanyang Technological University, 2021)
The intricate flow behaviour of a circular vortex-ring, at Re = 2000 and 4000, collision on a free surface from the bottom is studied numerically. Transient Large Eddy Simulation (LES) with the dynamic Smagorinsky sub-grid scale model alongside the Volume of Fluid (VOF) multiphase model were employed. Evaluation of the simulation against experimental studies shows that the fundamental characteristics of the flow were captured, while also presents further perspective in the three-dimensional flow visualization. The dynamics of secondary and tertiary vortex formation are observed to have connection with the baroclinic vorticity through the interfacial layer, such that air bubbles were swept along into the water. Furthermore, the vortex structures under the influence of diffusion at Re = 2000 and rapid eddy development at Re = 4000 were observed as gradual dissipation, which current experimental techniques could not capture at late time. This include the Crow, high wavelength, instability which strength is relative to the Reynolds number.